Hubungan Spiritualitas Guru Pendidikan Agama Kristen (PAK) dan Penelaahan Alkitab (PA) Terhadap Pembentukan Karakter Kristiani Siswa di SMP Negeri di Kecamatan Rimbo - Grace Skinantha S; Johari Manik; Hanna Dewi Aritonang; Sudirman Lase; Iwan Setiawan Tarigan (Jurnal Pendidikan Agama dan Teologi, 2024)
The purpose of this research is to 1) find out whether there is a relationship between the Spirituality of PAK Teachers and the Christian Character Formation of Teb State Middle School Students, 2) find out whether there is a relationship between Bible Study and the Christian Character Formation of Tebo State Middle School Students, 3) to find out whether there is a relationship between the Spirituality of PAK Teachers and Bible Study on the Formation of the Christian Character of Shiva SMP N Tebo. The research hypothesis is: "There is a significant relationship between PAK Teacher Spirituality and Bible Study on the Formation of Christian Character of N Tebo Middle School Students." The population is students of class VIII and IX of SMP N 3 Tebo, SMP N 30 Tebo, SMP N 31 Tebo totaling 290 people who are Christians. The research sample was determined using a purposive sampling technique, namely 36 students from class VIII and IX of SMP N Tebo as an experimental class using Religious Education and Bible Study Teacher Spirituality and 36 students from class XI MIPA 3 as a control class using normal treatment (conventional class). The instrument used in this research was a 50-item questionnaire. Research data for the questionnaire was analyzed using the average difference test formula (N-Gain Score). It was found that the average value for the experimental class was 82.4369 in the effective category. And the average value for the control class is 22.9433, which is in the ineffective category. Then carrying out an independent test using the t test obtained a value of t = 20.376> t table (α = 0.05; df = 70) = 2,000. Thus, it can be concluded that the research hypothesis is accepted, namely that there is a relationship between the Spirituality of Religious Education Teachers and Bible Study on the Formation of Christian Character in N Tebo Middle School Students, and H0 is rejected.